2015
DOI: 10.7860/jcdr/2015/12271.6035
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fluoride Retention Due to Most Commonly Consumed Estuarine Fishes Among Fish Consuming Population of Andhra Pradesh as a Contributing Factor to Dental Fluorosis: A Cross-Sectional Study

Abstract: Background: Fluoride in drinking water is known for both beneficial and detrimental effects on health. The principal sources of fluoride include water, some species of vegetation, certain edible marine animals, dust and industrial processes. The purpose of this study was to evaluate the fluoride retention of most commonly consumed estuarine fishes among fish consuming population of Andhra Pradesh. Materials and Methods:A cross-sectional study was conducted to evaluate the amount of fluoride retention due to te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 10 publications
(10 reference statements)
1
11
0
Order By: Relevance
“…Fish were an important part of the diet since the Settlement period but never as much as during the Catholic period (c. 1000-1550 AD) due to religious fasting (Kristjánsdóttir 2017). Since both fresh and dried fish are considerable sources of modern fluoride exposure (Shomar et al 2004;Marva 2011;Ganta et al 2015) diet could be implicated as a potential origin of the higher fluoride levels noted at Skriðuklaustur than at Skeljastaðir. The overall average bone fluoride concentration at Skeljastaðir was lower than expected, considering the sites proximity to the volcano Hekla, which is known to be a heavy fluoride (and mercury) emitter (Coderre and Steinthorsson 1970;Thorarinsson and Sigvaldason 1970;Thordarson and Larsen 2007).…”
Section: Fluoride Concentrationsmentioning
confidence: 99%
“…Fish were an important part of the diet since the Settlement period but never as much as during the Catholic period (c. 1000-1550 AD) due to religious fasting (Kristjánsdóttir 2017). Since both fresh and dried fish are considerable sources of modern fluoride exposure (Shomar et al 2004;Marva 2011;Ganta et al 2015) diet could be implicated as a potential origin of the higher fluoride levels noted at Skriðuklaustur than at Skeljastaðir. The overall average bone fluoride concentration at Skeljastaðir was lower than expected, considering the sites proximity to the volcano Hekla, which is known to be a heavy fluoride (and mercury) emitter (Coderre and Steinthorsson 1970;Thorarinsson and Sigvaldason 1970;Thordarson and Larsen 2007).…”
Section: Fluoride Concentrationsmentioning
confidence: 99%
“…The levels of these compounds in meat, fruits, and vegetables are usually low. Nonetheless, the concentrations in canned fish like salmon and sardine are elevated, with higher fluoride content in fish from the sea than in those from river water [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…are aquatic species their environment is at huge risk of containing fluoride "the amount of fluoride present in fishes is directly related to the amount of Fluoride in the habitat they live in." (Ganta et al, 2015) Thus, when consuming these fish a person would also be consuming a small quantity of fluoride. "Recent studies reported average fluoride values for fish close to 0.05 mg/100 g and a range of 0.01 to 0.17 mg/100 g." (Ganta et al, 2015) Consuming a large amount of these fish would result to dental fluorosis.…”
Section: Dental Fluorosismentioning
confidence: 99%
“…(Ganta et al, 2015) Thus, when consuming these fish a person would also be consuming a small quantity of fluoride. "Recent studies reported average fluoride values for fish close to 0.05 mg/100 g and a range of 0.01 to 0.17 mg/100 g." (Ganta et al, 2015) Consuming a large amount of these fish would result to dental fluorosis. "These results show a strong association between water fluoride concentration and the proportion of the population with dental fluorosis….…”
Section: Dental Fluorosismentioning
confidence: 99%
See 1 more Smart Citation